The Identifikasi Delineasi Oli Berdasarkan Nilai Resistivitas Menggunakan Metode Geolistrik Di Area “X” Tana Tidung, Kalimantan Utara - Wibowo, Nobella Hadi; Djayus, Djayus; Supriyanto, Supriyanto (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2023)
Waste pollution is a problem that must be addressed immediately. Apart from affecting the air and waters, sewage pollution can also seep below the ground surface. One of the causes of waste pollution in area